Innovative Soil Management and Micro-Climate Modulation for Saving Water in Peach Orchards - Campi, Pasquale; Gaeta, Liliana; Mastrorilli, Marcello; Losciale, Pasquale (Frontiers in Plant Science, 2020)
In semi-arid conditions, where water availability is limiting, the efficient management of irrigation water is a dramatic issue. The goal of efficiency can be reached by reducing water supply and water losses, as it has been clearly demonstrated from field studies on limited irrigation (L) or from studies on microclimate modifications.Roofing above the canopy or soil mulching can contribute to contain evapotranspiration and to increase water use efficiency. In Mediterranean areas, hail nets have become more and more common in high-income orchards. Nevertheless, covering materials can be multipurpose if the protection function is coupled to the modulation of orchard microclimate in order to meet plant needs and water saving. Plastic mulching reduces soil evaporation by cutting off the vapor transport path between the soil surface and the atmosphere as well as can contrast weed growth and the related evapotranspiration.The aim of this 2-year study, carried out on a late ripening peach (cv. California) growing in a typicalMediterranean horticultural area (from southern Italy), was to investigate the combined effect of water supply (regular and limited irrigation), incoming light modulation (through hail net or shading hail net) and soil management (tilling or and mulching by means of bio-films) on: microclimate; 2 productivity; irrigation water use efficiency (WUEI) and soil water stress coefficient (Ks). Ks stands for a transpiration reduction factor determined by monitoring the soil water status.Shading hail-net reduced air temperature (-1 °C), wind speed (-57%), solar radiation (-32%), while increased relative air humidity (+9.5%). Compared to the control crop management (hail net coverage, soil tillage and full irrigation), limited irrigation alone was able to slightly increase WUEI thanks to the reduction of water supply without any decrease of yield. The combination of shading hail net coverage, mulching and limited irrigation allowed to save the seasonal irrigation water volumes (-25%) with an increase in final yield (+ 36%) and in WUEI (+ 53%).In semi-arid environments, net shading and soil mulching, acting jointly, do mitigate soil water stress induced by limited irrigation suggesting that this innovative agro-technique could reduce irrigation needs and save water resource.